2018
DOI: 10.1051/0004-6361/201833386
|View full text |Cite
|
Sign up to set email alerts
|

The optical properties of dust: the effects of composition, size, and structure

Abstract: Context. Dust grains are determinant for setting the chemical, physical, dynamical, and radiative properties of all the media in which they are present. Their influence depends on the grain composition, size, and geometrical structure which vary throughout the lifecycle of dust. Particularly grain growth arises in dense molecular clouds and protoplanetary disks as traced by an enhancement of the dust far-IR emissivity and by the effects of cloudshine and coreshine. Aims. Our aim is to investigate the imprint o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 69 publications
1
49
1
Order By: Relevance
“…The asymmetry of the emission is suggestive of the in- ner region of a disc or torus seen nearly face on, consistent with the Northern sector of the outflow being closer to the observer and hence producing more flux through the difference in scattering phase function at different angles (e.g. Ysard et al 2018), although a spherical shell cannot be excluded on the basis of this data alone. Alternatively, the images may imply that there is significant clumpy or filamentary structure to the extended component, although additional, deeper observations would be required to determine whether these constitute discrete components in the ejecta or are artefacts.…”
Section: Resultssupporting
confidence: 56%
“…The asymmetry of the emission is suggestive of the in- ner region of a disc or torus seen nearly face on, consistent with the Northern sector of the outflow being closer to the observer and hence producing more flux through the difference in scattering phase function at different angles (e.g. Ysard et al 2018), although a spherical shell cannot be excluded on the basis of this data alone. Alternatively, the images may imply that there is significant clumpy or filamentary structure to the extended component, although additional, deeper observations would be required to determine whether these constitute discrete components in the ejecta or are artefacts.…”
Section: Resultssupporting
confidence: 56%
“…However, if all other parameters in Equation 3 are held fixed, higher metallicity (therefore higher fZ ) leads to lower values of κ500, meaning the trend for M 74 in Figure 16 is being driven by the data in spite of this. Greater ISM metallicity will lead to increased grain growth (Dwek 1998;Zhukovska 2014;Galliano et al 2018), and larger grains should give rise to larger values of κ d (Li 2005;Köhler et al 2015;Ysard et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…where κ λ is the value of κ d at a particular wavelength λ, κ0 is the value of κ d at a reference wavelength λ0, and β is the dust emissivity spectral index. Laboratory analysis of dust analogues and chemical modelling suggest that this relation is reliable in the wavelength range 150 λ 1000 µm; at wavelengths shorter than this the variation of κ d with wavelength becomes much more complex, whilst at longer wavelengths the behaviour of κ d is less clear, with some evidence of an upturn (Demyk et al 2017a,b;Ysard et al 2018). Figure 1 compiles a wide range of κ d values that have been reported in the literature (all have been converted to a reference wavelength of 500 µm as per Equation 2; we only plot values for which the original quoted reference wavelength was in the reliable 150-1000 µm range).…”
Section: Introductionmentioning
confidence: 99%
“…Mishchenko et al (2016a,b) performed exhaustive studies of the applicability of the Maxwell Garnett mix-1 See http://www.ias.u-psud.fr/themis/. 2 For the full details of the model see: Jones (2012a,b,c); Jones et al (2013); Köhler et al (2014Köhler et al ( , 2015; Jones et al (2016); Ysard et al (2016Ysard et al ( , 2018 ing rule to heterogeneous particles. These latter authors showed that this rule can provide accurate estimates of the scattering matrix and absorption cross-section of heterogeneous grains at short wavelengths (typically up to the visible for a 0.1 µm grain and to the mid-infrared (MIR) for a 10 µm grain) if two criteria are met: both the size parameter of the inclusions and the refractive index contrast between the host material and the inclusions have to be small.…”
Section: Dust Optical Propertiesmentioning
confidence: 99%
“…After exploring the effect of complex grain structures with a single chemical composition in Ysard et al (2018), the intent of this study is to investigate the effect of complex chemical compositions for isolated spherical grains up to very large sizes. This rather simple approach may not be too unrealistic in the case of very dense environments where grain-grain compaction and gas compression may be efficient processes (e.g.…”
Section: Introductionmentioning
confidence: 99%